A societal cost-benefit analysis of falls prevention in community-dwelling older people in the Netherlands - Martien J.M. Panneman; Ed F. van Beeck; Branko F. Olij; Juanita A. Haagsma; Frans van Zoest; Judith I. Kuiper; Suzanne Polinder (Experimental Gerontology)
Background: Aging populations face rising incidents of falls among older people, leading to increased healthcare costs. Preventive measures can reduce this burden and associated costs. However, implementing falls prevention interventions causes costs for society. In order to gain insight in the balance between investments and gains for society the Societal Cost Benefit Analysis (SCBA) methodology can be applied. We conducted a societal cost-benefit analysis (SCBA) of falls prevention interventions in the Netherlands in order to show the stepwise approach, data sources needed and analyses that characterize this method. Methods: We used SCBA to assess falls prevention interventions' costs and benefits for three stakeholders: private health insurance companies, the national government, and local government. We created five healthcare scenarios for falls prevention interventions, involving informal care, primary care, home care, social work, and an integral scenario. Our SCBA model considered all associated costs with case-finding, screening, and recruitment for each scenario, as well as multifactorial falls prevention programs' costs and benefits, such as reduced healthcare expenses and health gains (DALYs). Results: All scenarios lead to health gains, ranging from 90 averted DALYs in the informal care to 300 in the primary care scenario.The net benefits per 100,000 senior citizens of falls prevention programs range from €0.2- €5.6 million respectively for social care and home care scenario with benefit-cost ratios of respectively 1.1 and 2.5. Sensitivity analysis revealed that a lower age limit accompanied by a low initial fall risk for recruitment significantly influence the SCBA outcomes. Conclusion: Structural implementation of evidence-based falls prevention can provide significant health benefits and net cost savings, supporting its implementation at the societal level. The SCBA offers guidance to policymakers on the optimal falls prevention programs for older people, reducing the disease burden of falls in the Netherlands.